Achievement goal profiles in elementary school: antecedents, consequences, and longitudinal trajectories - Schwinger, Malte; Steinmayr, Ricarda; Spinath, Birgit (Contemporary educational psychology, 2016)
The present study investigated antecedents and consequences of achievement goal profiles across multiple measurement waves from second to fourth grade in a sample of 542 German elementary school students.